DOES GASTRONOMY BRAND IMAGE AFFECT THE PERCEIVED EMOTIONAL VALUE AND TOUR SATISFACTION? - Melih AYDIN; Hatice SARI GÖK; Simge SALVARCI (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Gastro-cultural tours, which are prevalent as part of today’s experience-based travel, generate memorable gastronomy encounters for tourists. Gastronomically designed cultural tours also shed light on the past's heritage and cultural identity through the local tastes of the regions by promising distinct stories and experiences to travelers. Regions with gastronomic affluence arouse gastro tourists’ interest with their cultural and tourist attractions. One of the critical factors contributing to the awareness of visitors towards a particular destination is the creation of a gastronomy brand image in their minds. A region with a gastronomy brand can also affect the emotional value tourists attribute to the region. From different perspectives, this cuisine-based brand image appears to have the potential to influence tourists' satisfaction with the tour. The Southeastern Anatolia Region, one of Turkey's most prominent culinary centers, is a diverse region with both indigenous gastronomic value and deep-rooted cultural history. From this point of view, the effects of gastronomy brand image on perceived emotional value and tour satisfaction of tourists taking part in gastro-cultural tours were examined in this study. According to the data obtained from the participants, gastronomy brand image has a significant effect on tour satisfaction and the perceived emotional value of the tourists.